Body size and the urban heat island effect modulate the temperature–size relationship in ground beetles. (12th July 2022) - Lövei, Gábor L.; Magura, Tibor
Abstract: Aim: Body size is a key trait linked to other life history traits and influences several individual‐, community‐ and ecosystem‐level characteristics, processes, functions and services. Ecological and evolutionary body size responses at the intra‐ and inter‐specific level to thermal geographic gradients (e.g. latitudinal or altitudinal ones) are widely studied. Whether this temperature‐size relationship remains true for community‐wide body size is still largely unknown. Location: Northern temperate region. Taxon: Ground beetles (Carabidae). Methods: We assessed the temperature‐size relationships using data from 11 northern temperate locations, spanning 25 latitudinal degrees. Furthermore, we quantified the effects of potential competing factors, such as body size and habitat preference of carabid assemblages and sub‐assemblages along urbanisation gradients, as well as the urban heat island (UHI) effect on this relationship. Results: We found significant negative relationship between the community‐wide mean body size and the geographical latitude (converse Bergmann cline) for the whole ground beetle assemblage and the sub‐assemblages of large‐bodied species. This relationship was stronger in the urban localities than in rural ones. For the sub‐assemblages of small‐sized species, the relationship was not significant. We found significant negative relationship between the community‐wide mean body size and the latitude for the sub‐assemblages of both the non‐forest and the forest species, and these became stronger in the urban habitats. Main Conclusions: Our results highlight the leading role of the individual body size and the UHI effect in determining the community‐wide body size–latitude relationship in ground beetles.